Engineering Biomechanics of Human Motion - Lalwani, Vijay Kishanchand; Upadhyay, Urvi Paras (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The concentration in biomechanics and human performance engineering provides the background and skills needed to create work and living environments which improve human health and enhance performance. The objectives of this is to provide a basic introduction to the anatomy and physiology of the human musculoskeletal system and then to cover the kinematics and dynamics of spatial multiple degree-of-freedom human motion.Internal and external forces acting on the human body have an impact on many factors ultimately affecting health.This study involves biomechanical influences on disease. Biomechanics can also be used to guide treatments for movement problems. Biomechanics is the science of the action of forces, internal or external on the living body.Statics is the study of forces on bodies at rest Dynamics is the study of the motion of bodies and the forces that produce the motion